Tetrapod and invertebrate trace fossils from aeolian deposits of the lower Permian of central-western Argentina - Krapovickas, Verónica (2015)
Abundant tetrapod footprints are described from the Early Permian Yacimiento Los Reyunos Formation including both collected and in situ specimens. The slabs come from several quarries at the Sierra Pintada and Sierra de las Peñas area, south-west of Mendoza, Argentina. The trace fossil assemblage, which constitutes one of the oldest known from Gondwana, comprises excellent-preserved tetrapod tracks (Chelichnusduncani, Chelichnusgigas and ‘pear-like’ footprints) and invertebrate simple sub-horizontal (Palaeophycustubularis) and vertical (Skolithos isp.) burrows formed in a aeolian dune field. The analysis of the tetrapod track producers indicates the presence of at least three different taxa of sprawling to semi-erect therapsids, thus suggesting the presence of members of this clade, or closest relatives, in the Early Permian of southern Gondwana. Moreover, a series of measurements and simple indexes were developed to estimate body proportions and locomotion styles of the putative trackmakers. The new assemblage, analysed in the context of other known Permian assemblages from Pangea, is one the few known in Gondwana to be present in an aeolian environment. The evaluation of the assemblage, in the light of aeolian ichnofacies (Chelichnus, Octopodichnus and Entradichnus), shows that it has common elements with the Chelichnus and Entradichnus ichnofacies.